Dynamic Evolution of Avian RNA Virus Sensors: Repeated Loss of RIG-I and RIPLET - Krchlíková, Veronika; Hron, Tomáš; Těšický, Martin; Li, Tao; Ungrová, Lenka; Hejnar, Jiří; Vinkler, Michal; Elleder, Daniel (Viruses, 2022)
Retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated protein 5 (MDA5) are key RNA virus sensors belonging to the RIG-I-like receptor (RLR) family. The activation of the RLR inflammasome leads to the establishment of antiviral state, mainly through interferon-mediated signaling. The evolutionary dynamics of RLRs has been studied mainly in mammals, where rare cases of RLR gene losses were described. By in silico screening of avian genomes, we previously described two independent disruptions of MDA5 in two bird orders. Here, we extend this analysis to approximately 150 avian genomes and report 16 independent evolutionary events of RIG-I inactivation. Interestingly, in almost all cases, these inactivations are coupled with genetic disruptions of RIPLET/RNF135, an ubiquitin ligase RIG-I regulator. Complete absence of any detectable RIG-I sequences is unique to several galliform species, including the domestic chicken (Gallus gallus). We further aimed to determine compensatory evolution of MDA5 in RIG-I-deficient species. While we were unable to show any specific global pattern of adaptive evolution in RIG-I-deficient species, in galliforms, the analyses of positive selection and surface charge distribution support the hypothesis of some compensatory evolution in MDA5 after RIG-I loss. This work highlights the dynamic nature of evolution in bird RNA virus sensors.
Keywords: Immunity, Innate; ptáci; Birds; DEAD Box Protein 58; RNA; innate immunity; RNA-viry; avian genome; DEAD box protein 58; zvířata; viral sensors; RNA Helicases; RNA Viruses; antivirové látky; Antiviral Agents; gene loss; RNA-helikasy; Animals; přirozená imunita